On the methodology of determining the transverse tensoresistance in multi-valley semiconductors - Gaidar, G.P. (Reports of the National Academy of Sciences of Ukraine, 2022)
The transverse (the current in the sample is oriented perpendicular to the deformation axis) and longitudinal (the current is directed along the deformation axis) tensoresistances of high-resistance n-Si crystals are investigated. The mobility anisotropy parameter was calculated for these two cases. The coincidence (within the experimental errors) of the obtained values of the parameter K was established when the current passes along the direction of deformation and perpendicular to it. Using n-Ge crystals, the reliability of the technique for measuring the transverse tensoresistance was confirmed by calculating the mobility anisotropy parameter using the data obtained from two independent experiments. A good agreement was obtained for the values of the anisotropy parameter K, calculated from the measurement data of only the longitudinal tensoresistance and from the measurement data of the longitudinal and transverse tensoresistances. It was experimentally confirmed that under conditions of strong elastic directional compressive deformation (in the absence of manifestation of the shift deformation components in n-Si crystals), only relative displacements of isoenergetic ellipsoids in multi-valley semiconductors along the energy scale occur, but the shape of the ellipsoids remains practically unchanged.